Effectivness of creative thinking module on figural creativity of engineering undergraduate in Malaysia - Long C.Y.; Balakrishnan B.; Ying C.P.; Yan K.Y. (Sciedu Press, 2023)
This research paper presents the outcome of research conducted to improve and enhance the creativity level of engineering undergraduates at a private institution of higher learning in Malaysia. A Creative Thinking Module that features six proposed creative thinking tools was developed and administered to a group of 3rd Year Mechanical Engineering Undergraduates in the studied university. The Torrance Test of Creative Thinking Figural Forms were applied to measure the creativity level of respondents in this research. The effects of the Creative Thinking Skills Module developed is obtained through Pre-Test and Post-Test research method, Paired Sample T-Test and Wilcoxon Signed-Rank test are used to analyse the scores, and results indicated the module developed has significantly improved the creativity of the undergraduates. 2020, Sciedu Press. All rights reserved.